Somatotropic Axis and Obesity: Is There Any Role for the Mediterranean Diet? - Muscogiuri, Giovanna; Barrea, Luigi; Laudisio, Daniela; Di Somma, Carolina; Pugliese, Gabriella; Salzano, Ciro; Colao, Annamaria; Savastano, Silvia (Nutrients, 2019)
Obesity is associated with reduced spontaneous and stimulated growth hormone (GH) secretion and basal insulin-like growth factor I (IGF-1) levels—which in turn is associated with increased prevalence of cardiovascular risk factors. The aim of this study was to investigate: (1) the association of somatotropic axis with cardiometabolic status; (2) the association of somatotropic axis with the Mediterranean diet and nutritional pattern in people with obesity. Cross-sectional observational study was carried out in 200 adult women, aged 36.98 ± 11.10 years with severe obesity (body mass index—BMI of 45.19 ± 6.30 kg/m2). The adherence to the Mediterranean diet and the total calorie intake was assessed. Anthropometric measurements, body composition and biochemical profile were determined along with Growth Hormone (GH)/Insulin like Growth Factor 1 (IGF-1) axis and insulin resistance (homeostatic model assessment for insulin resistance—HoMA-IR). The enrolled subjects were compared after being divided according to GH peak response and according to IGF-1 standard deviation scores (SDS). Derangements of GH peak were detected in 61.5% of studied patients while IGF-1 deficiency was detected in 71% of the population. Both blunted GH peak response and IGF-1 SDS were indicators of derangements of somatotropic axis and were associated with comparable results in terms of cardiometabolic sequelae. Both GH peak and IGF-1 levels were inversely associated with anthropometric and metabolic parameters. The adherence to the Mediterranean diet predicts GH peak response. Fatty liver index (FLI), fat mass (FM) and phase angle (PhA) were predictive factors of GH peak response as well. In conclusion derangements of somatotropic axis is associated with a worse cardiometabolic profile in people with obesity. A high adherence to the Mediterranean diet—and in particular protein intake—was associated with a better GH status.